Strategies for perioperative hypothermia management: advances in warming techniques and clinical implications: a narrative review - Nan Ji; Jiangtao Wang; Xiaohui Li; Yi Shang (BMC Surgery)
Abstract Perioperative hypothermia is a frequent clinical complication resulting from the cold environment of the operating room and prolonged skin exposure, leading to adverse outcomes and increased healthcare burdens. To address this issue, this narrative review discusses in detail the currently common warming strategies for perioperative hypothermia .Forced air warming (FAW) systems are widely recognized as the most effective intervention for maintaining core body temperature. Additionally, alternative technologies, such as circulating-water mattresses, carbon-fiber resistive heating systems, self-regulated heated air garments, self-heating blankets, and chemical heat packs, offer diverse advantages and disadvantages. Passive warming methods, including thermal reflective blankets and cotton blankets, provide a cost-effective solution, albeit with reduced efficacy compared to active warming measures. Recent advancements have focused on improving both active and passive warming approaches to balance effectiveness and cost-efficiency. While FAW remains the gold standard, other systems offer specific benefits, such as improved portability and reduced costs, making them suitable for use in diverse clinical scenarios. Effective perioperative temperature management reduces hypothermia-related complications, decreases healthcare expenditures, and provides substantial social and organizational benefits. Thus, selecting the most appropriate warming intervention in clinical practice requires a tailored approach, considering both patient-specific needs and resource availability.